STABILITY INDICATING RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF AMLODIPINE AND HYDROCHLOROTHIAZIDE IN PHARMACEUTICAL DOSAGE FORM - BHARATI, ASHWINI R.; DESHMANE, SUBHASH V.; BIYANI, KAILSH R. (International Journal of Current Pharmaceutical Research, 2015)
Objective: The aim of present work is to develop a simple, selective and precise, stability indicating RP-HPLC method for the simultaneous estimation of Amlodipine and Hydrochlorothiazide. Methods: The chromatographic separation of the two drugs was achieved on a reverse phase Hypersil Gold, C18, 250 × 4.6 mm, 5μm column using mobile as Potassium dihydrogen buffer–Acetonitrile in ratio of 600:400 v/v (pH adjusted to 3.2±0.05 using orthophosphoric acid) with flow rate of 1.0 ml/min with injection volume 20 μl and the detection was carried out at 237 nm using UV detector. Results: The retention time of amlodipine (Amlo) and hydrochlorothiazide (HCT) were found to be 3.80 and 6.48 min respectively. The linear regression analysis data for the calibration plots showed good linear relationship in the concentration range of 0.84-1.98 μg/ml for hydrochlorothiazide and 4.2-9.8 μg/ml for amlodipine. Conclusion: The method was validated for precision, linearity, LOD and LOQ, specificity, accuracy, system suitability and ruggedness as per ICH guidelines and the results were found to be within the limits. The developed method was used for the stability studies. The validated method can be used for routine quality control testing for HCT and Amlo combine dosage form.